Diffuse pulmonary angiomatosis. Issue 11 (November 1991) - Canny, G J; Cutz, E; MacLusky, I B; Levison, H
Abstract : A six year old girl with diffuse pulmonary angiomatosis presented with haemoptysis and diffuse interstitial changes with bilateral pleural effusions on the chest radiograph. The lung lesion as seen on biopsy specimens (and confirmed at necropsy) consisted of bloodless, thin walled, endothelium lined channels, affecting the interstitial septae, pleura, bronchi, and adventitia of large vessels. There was no response to oral corticosteroids or a trial of cyclosphamide. This lesion may be an example of an angiogenic disease.